Multi-temporal analysis of changes in land use in Santa Cruz Island, Galapagos archipelago, period 1991 - 2023 - González Soto, Fernando (2024)
The change in land use resulting from human activities occurs at both global and local scales. The present research focuses on the multi-temporal analysis of land use change on Santa Cruz Island, Galápagos. Therefore, the analysis of land uses and their transition with vegetation cover was proposed to examine their evolution. Geographic Information Systems and the Supervised Classification technique were employed to identify changes in the terrain over time and the factors responsible for these alterations. In order to obtain accurate information about existing land uses in the study area, free satellite images were used, allowing the distinction of four distinct classes. Through this analysis, it was possible to determine the evolution of land use over a period of 32 years, spanning from 1991 to 2023. The results revealed that the classified areas underwent modifications due to both natural and human-induced factors, including livestock and agricultural activities, as well as demographic growth.  To validate the obtained data, a confusion matrix was conducted, and the Kappa index was applied. These procedures demonstrated the robustness and agreement of the model used, ensuring high accuracy compared to reality.  In conclusion, this study provides a comprehensive view of land use change on Santa Cruz Island, Galápagos, and offers relevant information about the factors that have contributed to such changes over time. The results have significant implications for sustainable land management and ecosystem conservation in this important region.